2003
DOI: 10.1053/jhep.2003.50343
|View full text |Cite
|
Sign up to set email alerts
|

A Liver Tolerates A Portal Antigen by Generating Cd11c+ Cells, Which Select Fas Ligand+ Th2 Cells Via Apoptosis

Abstract: Administration of an antigen (Ag) per oral route leads to apoptosis of Ag-specific CD4 ؉ T cells and to development of Th2 cells expressing Fas ligand (FasL) in the liver. We determined whether presentation of an ingested Ag in the liver alone was enough to select these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…Previous studies have shown that IL-12 not only drives Th1 differentiation but also inhibits T cell apoptosis of newly differentiated cells and thereby enhances their survival (Fuss et al, 1999;Watanabe et al, 2003). We therefore asked whether presentation of OVA peptide by PGN-stimulated NOD2-deficient APCs (CD11b + cells) to OVA-specific CD4 + T cells (OT-II T cells) affects the apoptosis of the T cells.…”
Section: Pgn-stimulated Nod2-deficient Apcs Is Associated With Decreamentioning
confidence: 97%
“…Previous studies have shown that IL-12 not only drives Th1 differentiation but also inhibits T cell apoptosis of newly differentiated cells and thereby enhances their survival (Fuss et al, 1999;Watanabe et al, 2003). We therefore asked whether presentation of OVA peptide by PGN-stimulated NOD2-deficient APCs (CD11b + cells) to OVA-specific CD4 + T cells (OT-II T cells) affects the apoptosis of the T cells.…”
Section: Pgn-stimulated Nod2-deficient Apcs Is Associated With Decreamentioning
confidence: 97%
“…Given the fact that 90% of BM cells express the double mutations above, it is likely that BM-derived cells from this patient show both enhanced pro-inflammatory responses and resistance to apoptosis. To test this hypothesis, BM-derived peripheral blood monocytes were stimulated with toll-like receptor (TLR) ligands such as peptidoglycan (PGN, a TLR2 ligand), Pam 3 CSK4 (a TLR2 ligand) and lipopolysaccharide (LPS, a TLR4 ligand) to measure the percentage of apoptotic cells and the production of pro-inflammatory cytokines as described previously [12,13,14]. The percentages of annexin V + apoptotic monocytes were markedly reduced in the patient upon stimulation with PGN and LPS compared with those of the healthy control (fig.…”
Section: Case Reportmentioning
confidence: 99%
“…In addition, oral administration of Ag was found to result in massive apoptosis of Ag-specific CD4 + T cells in the liver and the emergence of T regs producing IL-4, IL-10 and TGF-b [139]. The finding that hepatic CD11c + cells that have captured ingested Ag can induce T cell apoptosis and Th2/T regs differentiation both in vitro and upon adoptive transfer suggests a critical role of liver DCs in oral tolerance induction [140]. At least four DC subsets were recently identified within the liver, including myeloid CD11c + CD8a -DCs and CD11c + CD8a + lymphoid DCs that displayed potent T cell stimulatory abilities similar to their splenic counterparts [141].…”
Section: A Role For the Liver Dcs?mentioning
confidence: 98%